Pelaksanaan Pengawasan Dinas Perhubungan Dalam Menertibkan Kendaraan Nomor Polisi Luar Daerah Di Kabupaten Mandailing - Asrul Siregar; Hasbullah Malau (Jurnal Teori dan Riset Administrasi Publik, 2020)
This study aims to find out and obtain an overview of the implementation of supervision of the Transportation Agency in order to control vehicles with outside police numbers that reside and operate in Mandailing Natal District. This study used descriptive qualitative method. The results showed that the supervision carried out by the Transportation Agency in curbing vehicles with police numbers outside the area that settled in Mandailing Natal District had not been maximized. according to what has been regulated in Law number 22 of 2009. So that the potential loss and damage will occur due to vehicles with outside police numbers operating in the area and staring in the Mandailing Natal Regency, it could increase.